Predictors of institutional delivery service utilization among women in Northern region of Ghana - Abdul Gafaru Mohammed; Ruth Nimota Nukpezah; Harriet Bonful; Hilarius Paul Asiwome Kosi Abiwu; Charles Lwanga Noora; Alice Sallar Adams; Jennifer Nai-Dowetin; Ernest Kenu (PLoS ONE, 2025)
Introduction An increase in home delivery among expectant mothers may likely lead to high maternal and newborn morbidities and mortalities. Despite the policy on free maternal healthcare in Ghana under the National Health Insurance Scheme (NHIS) since 2007, more than 25% of deliveries still occur outside health facilities in northern Ghana. Use of safe and effective delivery services including place of delivery is an important component of the Safe Motherhood concept. Hence, assessing predictors of institutional delivery could contribute to improving birth outcomes in the Northern Region. Methods We conducted a community-based cross-sectional survey of 310 women aged 15–49 years old who had given a live birth between January 2022 and January 2023, using a simple random sampling approach. Using a semi-structured questionnaire, we collected data on mothers’ background characteristics, place of delivery for their most recent birth and reported health facility factors. Descriptive analyses and multiple logistic regression models were performed to identify factors associated with institutional delivery at a 5% significance level. Results Of 310 women in the study, the prevalence of institutional delivery was 79%(245) in their most recent births. More than 60%(200/310) of the women were married and 53%(163/310) had no formal education. Being married (adjusted odds ratio {aOR}=2.8, 95%CI:1.48–5.32), the presence of skilled health personnel at post (aOR=2.9, 95%CI:1.54–5.43), reported positive attitude of health workers towards their clients (aOR=1.8, 95%CI:1.03–3.23) and positive community perception of health facility delivery (aOR=3.8, 95%CI:1.64–8.71) were associated with increased odds of institutional delivery. Conclusions Our study identified multiple predictors of institutional delivery; marital status, the presence of skilled health personnel at health facilities, the perceived attitude of health workers and community perception. The research team organized discussions on institutional delivery services with community members in five selected districts in the region. We recommend the Ministry of Health should develop well-defined care packages targeting unmarried pregnant women, negative health worker attitudes and negative community perceptions.